Effects of the pandemic on the care of patients with colorectal cancer - Reinacher-Schick, Anke Claudia; Ebert, Matthias; Piso, Pompiliu Ioan; Hüppe, Dietrich; Schmitt, Jochen Maximilian; Schildmann, Jan (Deutsches Ärzteblatt, 2023)
Background: During the COVID-19 pandemic, there was a decrease in the rates of diagnosis and treatment of cancer. However, only a few detailed analyses have been made to date regarding the effect of the pandemic on the care of cancer patients in Germany. Such studies are needed as the basis for well-founded recommendations on health-care delivery priorities during pandemics and other, comparable situations of crisis. Methods: This review is based on publications that were retrieved by a selective search of the literature for controlled studies from Germany on the effects of the pandemic on colonoscopies, first diagnoses of colorectal cancer (CRC), surgical procedures for CRC, and CRC-related mortality. Results: Compared to 2019, the rate of screening colonoscopies performed by physicians in private practice was 1.6% higher in 2020 and 4.3% higher in 2021. On the other hand, the rate of diagnostic colonoscopies in the inpatient setting was 15,7% lower in 2020, while that of therapeutic colonoscopies was 11.7% lower. According to the data evaluated here, first diagnoses of CRC were 2.1% less common in January to September in 2020 than they had been in 2019; according to routine data collected by the statutory health insurance provider GRK, surgery for CRC was 10% less common in 2020 than in 2019. With regard to mortality, sufficient data from Germany were lacking to draw definite conclusions. International modeling data suggest an increase in mortality due to decreased colorectal screening rates during the pandemic that may at least be partially compensated for by intensified screening strategies following the pandemic. Conclusion: Three years after the onset of the COVID-19 pandemic, there is still only a limited evidence base for an evaluation of the effects of the pandemic on medical care and on the outcomes of patients with CRC in Germany. The implementation of central data and research infrastructures will be necessary for further study of the long-term effects of this pandemic, as well as to enable optimal preparedness for future crisis situations.
Gesehen am 27.02.2024